Life Motivation in Autobiography of Nick Vujicic Life Without Limits Literary Learning Perspective - Rifka Meluwu; Intama J. Polii; Mayske R. Liando (Journal of Social Science, 2022)
This study describes Nick Vujicic's life motivation which includes extrinsic and intrinsic motivation to fulfill his life needs in his autobiography "Life Without Limits" from a literary learning perspective. The research method used is descriptive qualitative. The research results in Nick Vujicic's autobiography "Life Without Limits" show that Nick gets extrinsic motivation from his family, especially his father and mother, who encourage, mobilize, and direct Nick to make ends meet. Motivation from his parents encourages Nick to get the intrinsic motivation within himself to encourage himself to carry out his daily activities (physiological needs), feel secure about his future (need for security and protection), and feel loved and accepted by himself. Friends and family (the need to have and love) with a physical condition without arms and legs. Extrinsic and intrinsic motivation plays an important role that needs and complements each other in facing every difficulty and challenge in life, thus enabling Nick to fulfill his life's needs and get through his dark times